2014
DOI: 10.1016/j.brainresbull.2013.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of memory – From the adrenal medulla to liver to astrocytes to neurons

Abstract: Epinephrine, released into blood from the adrenal medulla in response to arousing experiences, is a potent enhancer of learning and memory processing. This review examines mechanisms by which epinephrine exerts its effects on these cognitive functions. Because epinephrine is largely blocked from moving from blood to brain, it is likely that the hormone's effects on memory are mediated by peripheral actions. A classic effect of epinephrine is to act at the liver to break down glycogen stores, resulting in incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 148 publications
(212 reference statements)
1
32
0
Order By: Relevance
“…There is now substantial evidence, as reviewed recently (Gold and Korol, 2012; Gold, 2014), showing that increased blood glucose levels in response to increases in epinephrine levels reflects a key mechanism linking epinephrine to memory. In a set of fundamental and classic experiments in biology, Sutherland and Rall (1960) showed that epinephrine activates hepatic adrenergic receptors to initiate the breakdown of glycogen to glucose with subsequent release of glucose into blood; it is these experiments that provided the first evidence for second-messenger systems in response to activation of cell membrane receptors.…”
Section: Background: Epinephrine and Glucose Modulation Of Memory Promentioning
confidence: 99%
See 2 more Smart Citations
“…There is now substantial evidence, as reviewed recently (Gold and Korol, 2012; Gold, 2014), showing that increased blood glucose levels in response to increases in epinephrine levels reflects a key mechanism linking epinephrine to memory. In a set of fundamental and classic experiments in biology, Sutherland and Rall (1960) showed that epinephrine activates hepatic adrenergic receptors to initiate the breakdown of glycogen to glucose with subsequent release of glucose into blood; it is these experiments that provided the first evidence for second-messenger systems in response to activation of cell membrane receptors.…”
Section: Background: Epinephrine and Glucose Modulation Of Memory Promentioning
confidence: 99%
“…Epinephrine administered near the time of behavioral testing enhances learning and memory across a wide spectrum of tasks in rodents (cf. Gold, 2008, 2014) and also enhances the durability of long-term potentiation (Korol and Gold, 2008). Administration of epinephrine also enhances memory in humans (Cahill and Alkire, 2003; Cahill et al, 2003).…”
Section: Background: Epinephrine and Glucose Modulation Of Memory Promentioning
confidence: 99%
See 1 more Smart Citation
“…Low doses of epinephrine have little effect on memory, moderate doses enhance memory, and high levels impair memory. One of the possibilities, regarding the mechanisms by which epinephrine can influence brain functions, is through the activation of β-adrenergic receptors on afferent neuronal axons of vagus nerve that media tes glucose release [31]. Additionally, the role of norepinephrine was confirmed in mediating the actions of other stress hormones on the preservation of memory (including epinephrine and glucocorticoids) [32].…”
Section: Plasma Level Of Corticosterone (а) Testosterone (в) Epinepmentioning
confidence: 99%
“…Thus, earlier it has been shown that epinephrine, released into blood from the adrenal medulla in response to stress, is a potent and dose-dependent enhancer of learning and memory processing [31]. Low doses of epinephrine have little effect on memory, moderate doses enhance memory, and high levels impair memory.…”
Section: Plasma Level Of Corticosterone (а) Testosterone (в) Epinepmentioning
confidence: 99%